2018
DOI: 10.1371/journal.pone.0199842
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cnidarian biofouling on salmon gill health and development of amoebic gill disease

Abstract: This study examines the potential implications of biofouling management on the development of an infectious disease in Norwegian farmed salmon. The hydroid Ectopleura larynx frequently colonises cage nets at high densities (thousands of colonies per m2) and is released into the water during regular in-situ net cleaning. Contact with the hydroids’ nematocysts has the potential to cause irritation and pathological damage to salmon gills. Amoebic gill disease (AGD), caused by the amoeba Paramoeba perurans, is an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 52 publications
0
41
0
Order By: Relevance
“…Direct contact with cnidarian biofouling can be harmful to the fish, as organisms bearing nematocysts (stinging cells), such as the hydroid Ectopleura larynx and the anemone Anthothoe albocincta, have the potential to cause gill and skin damage (Baxter et al 2012;Wybourne 2013;Bloecher, Powell, et al 2018). In addition, biofouling poses a health risk to cultured fish as it can facilitate and amplify the presence of pathogens by harbouring viral, bacterial, and parasitic organisms that cause various diseases (reviewed in Fitridge et al 2012).…”
Section: Biofouling and Associated Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct contact with cnidarian biofouling can be harmful to the fish, as organisms bearing nematocysts (stinging cells), such as the hydroid Ectopleura larynx and the anemone Anthothoe albocincta, have the potential to cause gill and skin damage (Baxter et al 2012;Wybourne 2013;Bloecher, Powell, et al 2018). In addition, biofouling poses a health risk to cultured fish as it can facilitate and amplify the presence of pathogens by harbouring viral, bacterial, and parasitic organisms that cause various diseases (reviewed in Fitridge et al 2012).…”
Section: Biofouling and Associated Pathogensmentioning
confidence: 99%
“…Upon contact, cnidarian biofoulers expel nematocysts that can penetrate fish skin and deliver poison (Helmholz et al 2010;Cegolon et al 2013), even after fragmentation following pressure-washing . For example, the hydroid Ectopleura larynx causes gill injuries in Atlantic salmon (Baxter et al 2012;Bloecher, Powell, et al 2018), and white-striped anemones Anthothoe albocincta are suspected to cause skin damage in Chinook salmon (Wybourne 2013). Management methods for other issues (eg parasitic sea lice) can further exacerbate these impacts.…”
Section: Net Cleaning and Exchangementioning
confidence: 99%
“…In addition to the presence of putative pathogens, a number of other potential risk factors for CGD have been proposed. One major type of risk factor may be environmental insult to the gills, such as exposure to harmful phytoplankton, gelatinous zooplankton species in the water column or biofouling organisms dislodged into pens during in situ net washing (Rodger et al 2011a; Bloecher et al 2018; Kintner & Brierley 2019). Bath treatments involving the use of chemotherapeutants such as formalin (Speare et al 1997) or hydrogen peroxide (Kiemer & Black 1997; Rodger et al 2011a) can be directly damaging to gills or may exacerbate existing gill conditions and may represent a risk factor for the development of CGD.…”
Section: Complex Gill Disease and Related Syndromesmentioning
confidence: 99%
“…To counter this, nets can be cleaned using pressure washers, but fish in cages have been observed to exhibit avoidance behaviour from the dense clouds of debris that come off the nets during the cleaning process. Experimental challenges showed that this debris can cause pathological changes in the gills, such as epithelial sloughing, necrosis and haemorrhaging (Baxter et al 2012; Bloecher et al 2018).…”
Section: Specific Types Of Marine Salmonid Gill Diseasementioning
confidence: 99%
“…Finally, Bloecher et al [56] recently confirmed the negative impact that the hydroid nematocyst Ectopleura larynx can have on salmon gill health and highlighted the potential risks that net cleaning poses to fish welfare. However, in situ measurements of gill health before and after net cleaning conducted in the field are necessary to validate these findings.…”
Section: Pathogens Involved In Cgdmentioning
confidence: 95%